Personal oficina de contabilidad. (UNED, 2023)
De izquierda a derecha, de pie Jefry Rodríguez Gómez, Jose Luis Marín Herrera, Silvana Martínez (secretaria), Delio Mora Campos, Leonel Banegas Argüelles (jefe), sentados Juan Carlos Zuñiga Pérez, José Alberto Ramírez Villalobos, Carlos Chaves Quesada, Luis Paulino Calderón Sibaja